Dinamika Populasi Terumbu Karang di Kawasan Nusa Penida Bali sebagai Indikator Kesehatan Ekosistem Laut - I Gede Arya Pradana; Ni Made Sari Utami; I Wayan Putra Mahendra (Journal of Marine Fisheries, 2025)
Coral reefs are essential marine ecosystems that provide habitat, coastal protection, and significant economic value. The Nusa Penida Marine Protected Area (MPA) in Bali has been recognized as one of Indonesia’s most diverse coral ecosystems. However, increasing human activities such as tourism, coastal development, and fishing pressure have affected the health and population dynamics of coral reefs. This study aims to analyze the changes in coral population structure in Nusa Penida as an indicator of marine ecosystem health. Data were collected using line intercept transect (LIT) and photo-quadrat methods at four monitoring sites between 2022–2024. The results show a decline in live coral cover by 8.4% in the last two years, with significant variations across depth gradients and reef zones. Acropora and Porites species dominated shallow areas, while massive coral species exhibited higher resistance to thermal stress. The findings highlight the importance of sustained monitoring and adaptive management to maintain coral resilience. These results provide insights for policymakers and conservation programs in enhancing coral reef restoration and ecosystem-based management in Bali’s marine conservation zones.